Kemampuan translasi representasi matematis mahasiswa dalam menyelesaikan statistika di perguruan tinggi negeri - Rahmawati, Azizah Nur Laily; Anwar, Lathiful; Sa'dijah, Cholis; Permadi, Hendro (UNIVERSITAS NEGERI MALANG, 2023)
Translation is a process of transforming information from source representation to target representation. The translation process is described in four activities, such as unpacking the source, preliminary coordination, constructing the target, and determining equivalence. This study aims to analyze and describe the translation process of mathematical representations from verbal to symbolic in UM Mathematics S1 students in solving statistics on variance and standard deviation material. The instruments used were translation test questions and interview guidelines. Data analysis focused on four translation activities which were then categorized (high, medium, low). The results of the research percentage show that 78.58 percent of students experience difficulties in translating representations from verbal to symbolic in statistical problems. This is because students make mistakes in interpretation and implementation. While 21.42 percent of students succeeded in translating representations in solving the variance and standard deviation problems that have been presented. In terms of categorization, 21.42 percent of students belong to the high category, 39.29 percent of students belong to the medium category, and 39.29 percent of students belong to the low category. At this stage, the researcher obtained 28 student subjects for further analysis through 4 (four) stages of translation.